2019
DOI: 10.3390/pr7090573
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Green Supplier Selection Approach under a Q-Rung Interval-Valued Orthopair Fuzzy Environment

Abstract: As enterprises pay more and more attention to environmental issues, the green supply chain management (GSCM) mode has been extensively utilized to guarantee profit and sustainable development. Green supplier selection (GSS), which is a key segment of GSCM, has been investigated to put forward plenty of GSS approaches. At present, enterprises prefer to construct the large-scale teams of decision makers to obtain the more reasonable ranking results during GSS process. However, the existing methods pay little att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 66 publications
(106 reference statements)
1
15
0
Order By: Relevance
“…e negative ideal group opinion is obtained by (42) and the calculated results are listed in Table 6.…”
Section: E Calculated Results By the Developed Methodmentioning
confidence: 99%
“…e negative ideal group opinion is obtained by (42) and the calculated results are listed in Table 6.…”
Section: E Calculated Results By the Developed Methodmentioning
confidence: 99%
“…Mohammadi et al [64] presented a group decision-making method for evaluating and ranking green suppliers, in which the relative preference relation was employed to weight selection criteria and the interval type-2 fuzzy MULTIMOORA method was applied for selecting the best green supplier. Liu et al [65] developed a large-scale green supplier selection approach based on q-rung interval-valued orthopair fuzzy sets and the MUL-TIMOORA method, and Liou et al [66] reported a datadriven green supplier evaluation model using the random forest algorithm, the DEMATEL-based ANP, and the multiobjective optimization on the basis of ratio analysis to the aspiration level (MOORA-AS) method.…”
Section: Compromise Methodsmentioning
confidence: 99%
“…Liu et al. [48] proposed IVq-ROF multi-objective optimization based on ratio analysis plus the full multiplicative form (IVq-ROF-MULTIMOORA) method. Darko and Liang [49] introduced some q-ROF Hamacher aggregation operators and demonstrated their application by developing q-ROF Evaluation Based on Distance from Average Solution (EDAS) method.…”
Section: Literature Reviewmentioning
confidence: 99%